2014
DOI: 10.1039/c4fo00211c
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of rhizome of Ligusticum chuanxiong Hort. (chuanxiong) enhances endothelium-dependent vascular reactivity in ovariectomized rats fed with high-fat diet

Abstract: The rhizome of Ligusticum chuanxiong Hort. (LC), also known as chuanxiong, is a very common herb widely used to treat cardiovascular and cerebrovascular diseases. It is also used as a major ingredient in soups for regular consumption to promote good health. To study the protective effect of LC ethanolic extract (LCEE, 600 mg per kg per day, p.o.) on the integrity of the vascular system, ovariectomized (OVX) rats were fed with a high-fat diet (HFD) plus LCEE for 12 weeks. The animal model was used to mimic the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…More than 61 % (67,373 of 109,486) unigenes were annotated by sequence similarity search in public databases. The percentages of the annotated unigenes were similar to those in Chinese fir (Huang et al 2012), parsley (Li et al 2014a, b) and tea (Shi et al 2011).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…More than 61 % (67,373 of 109,486) unigenes were annotated by sequence similarity search in public databases. The percentages of the annotated unigenes were similar to those in Chinese fir (Huang et al 2012), parsley (Li et al 2014a, b) and tea (Shi et al 2011).…”
Section: Discussionsupporting
confidence: 49%
“…Ono et al 2011;Tang et al 2011). To our knowledge, only a few transcriptome databases have been obtained from celery (Fu et al 2013), carrot (Iorizzo et al 2011) and parsley (Li et al 2014a, b) in the Apiaceae family, which were belonged to Apium, Daucus and Petroselinum genus, respectively. The limited resources cannot provide more help to study the L. chuanxiong, which is belonged to Ligusticum genus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanshinone has been reported to inhibit the production of inflammatory cytokines, protect endothelial cells, exert antioxidant activity and inhibit cell apoptosis (56). Similarly, Ligustrazine was able to attenuate the apoptosis of vascular tissue cells by inhibiting the formation of large quantities of OFR during the oxidative stress response, and ameliorate vascular endothelial injury due to oxidative stress (57). Furthermore, Ligustrazine was reported to reduce the secretion of TNF-α and IL-6 from LPS-induced macrophages (58).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, fingerprint analysis based on chromatography has been widely used for authentication and quality control of herbal drugs [20][21][22]. LCH extracts have been widely studied in animal models, both in vivo and in vitro to determine their cardiovascular function [23,24]. It has been found that, some traditional Chinese medicines such as Panax Quinquefolium Saponin can reverse myocardial ischemia [25].…”
Section: Introductionmentioning
confidence: 99%